Early detection of Huntington's disease. Blink reflex and levodopa load in presymptomatic and incipient subjects. Issue 1 (January 1981) - Esteban, A; Mateo, D; Giménez-Roldán, S
Abstract : The R2 response on the blink reflex was found to be abnormal in seven out of 17 Huntington's disease descendants. Such abnormalities were present in four untreated subjects and in three further subjects after administration of a single oral dose of levodopa-carbidopa. An increase in latency and differential latency (four cases), or in a single one of these parameters (three cases) were the abnormalities found, resembling findings in four incipient cases detected during routine family surveys. Continuous administration of levodopa-carbidopa over a 10-20 day period did not induce new characteristics in the blink reflex, nor increase those detected previously, and no case developed chorea. We suggest that the analysis of the blink reflex after a single oral levodopa-carbidopa dosage could provide an objective and quantifiable method for the detection of individuals at risk for Huntington's disease.